The Use of a Multi-Drug Therapy (MDT) Monitoring Calendar as a Medium to Support Medication Adherence in Leprosy Patients - Marianti Agustina Gudipun; Yoany Maria Vianney Bita Aty; Maria Selestina Sekunda; Aries Wawomeo; Florentianus Tat; Aben B.Y. Romana (Viva Medika, 2026)
Background: Treatment of leprosy with Multi-Drug Therapy (MDT) requires a relatively long duration, depending on the type of leprosy. The extended treatment period often leads to patient fatigue, which may reduce medication adherence and increase the risk of treatment discontinuation. This situation can hinder therapeutic success and elevate the risk of disease transmission and disability. Therefore, simple and practical strategies are needed to support patients in maintaining adherence throughout the treatment period. One potential strategy is the use of an MDT monitoring calendar as a reminder and monitoring tool. This study aimed to determine the effect of the MDT monitoring calendar on medication adherence among leprosy patients in Ende Regency. Methods: This quantitative study employed a pre-experimental one-group pre-test–post-test design. Total sampling was used, involving 16 respondents. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: All respondents demonstrated an increase in medication adherence after the implementation of the Multi-Drug Therapy (MDT) monitoring calendar, with no observed decrease in adherence. The Wilcoxon Signed-Rank Test indicated statistically significant results (Z = −3.532; p < 0.05), confirming the effect of the MDT monitoring calendar on medication adherence among leprosy patients in Ende Regency. Conclusion: The implementation of the Multi-Drug Therapy (MDT) monitoring calendar significantly improved medication adherence among leprosy patients. The MDT monitoring calendar can serve as an effective and easily implementable health promotion tool to support treatment success. Health service facilities are encouraged to integrate the MDT monitoring calendar into the leprosy control program in Ende Regency